Perancangan dan Pembuatan E-Commerce Berbasis Web pada UMKM Bebek Perantau Khas Madura di Jakarta Pusat - Putri, Tania Panca; Fauziyah, Fauziyah; Valentine, Hany Maria (Eksplorasi Teknologi Enterprise dan Sistem Informasi (EKSTENSI), 2023)
Fried duck, a signature dish from Madura, is highly renowned. This duck is typically cooked with distinctive spices and served with sambal and rice. The Micro, Small, and Medium Enterprises (MSME) 'Bebek Perantau Khas Madura' restaurant operates through direct on-site orders, limiting consumers' accessibility to processed duck food products. This research is motivated by the access constraints faced by certain consumers who find it challenging to spare time to visit the physical restaurant located at Jl. Citarum, Central Jakarta. The E-Commerce platform is anticipated to broaden consumers' access to the products and services offered by 'Bebek Perantau Khas Madura' restaurant in Jakarta. This research adopts the Software Development Life Cycle (SDLC) approach utilizing the Unified Modeling Language (UML) to design the E-Commerce platform. This platform is constructed using the PHP programming language with MySQL. An E-Commerce design solution is formulated to facilitate business interaction between consumers and the restaurant. Through this E-Commerce platform, it is expected that there will be an increase in the accessibility of products and services offered by 'Bebek Perantau Khas Madura' among consumers in Central Jakarta. The utilization of the E-Commerce platform as an alternative for ordering processed duck food products opens new opportunities for MSMEs to expand their market digitally. The successful implementation of this platform can reduce physical access barriers and enhance efficiency in business transactions.